The global prevalence of Toxocara canis among red foxes (Vulpes vulpes): A systematic review and meta-analysis - Celia V. Holland; Zahra Geraili Afra; Soghra Valizadeh; Maryam Ebrahimi; Ali Rostami (International Journal for Parasitology: Parasites and Wildlife, 2024)
Red foxes play a crucial role in the life cycle and transmission of zoonotic pathogens, including Toxocara canis; however, comprehensive information on the prevalence of T. canis in red foxes (Vulpes vulpes) is lacking. In this meta-analysis we aimed to evaluate the global and regional prevalence of T. canis among red foxes. We searched PubMed, Scopus, and Google Scholar for studies reporting prevalence of T. canis in red foxes up to April 1, 2024. Using a random-effects model, we estimated pooled prevalences at global, regional, and national levels and assessed heterogeneity through subgroup and meta-regression analyses. The overall pooled global prevalence of T. canis infection in red foxes was 32.1% (95% CI, 28.5–35.6%), with the highest prevalence in Europe (34.6%, 30.9–38.3%) and the lowest in the Eastern Mediterranean (20.0%, 11.0–29.0%). In other regions, prevalences of Toxocara were as follows: Central Asia (33.1%, 26.8–39.4%), North America (23.6%, 10.6–36.6%), Western Pacific (21.3%, 5.2–37.4%), and Eastern Mediterranean & North Africa (20.0%, 11.0–29.0%). However, data from certain geographical regions are very limited (for example Greece, Austria, China and North Africa). Prevalence rates showed a decreasing trend over time. Subgroup analyses indicated higher prevalences in male red foxes (54.1%, 41.4–66.7%) compared to females (37.5%, 29.9–45.1%), and in juvenile red foxes (56.2%, 39.1–73.3%) compared to adults (33.4%, 23.2–43.6%). T. canis worm burdens were generally low, not exceeding an average of 4 worms per fox in most studies. Our findings reveal a substantial prevalence of T. canis infection in red fox populations worldwide (32.1%), highlighting their potentially significant role in perpetuating the transmission of infection to both companion animals and humans. Continued surveillance is essential to mitigate the risk of Toxocara transmission to companion animals and humans. However, a major remaining challenge is to assess the relative importance of the red fox as a contributor to environmental contamination with Toxocara ova. Further research is also needed to address study limitations and provide a complete global picture of T. canis epidemiology in red foxes and other wild animals, especially in underrepresented regions.